Comparing the Support-Efficacy Model among Centenarians Living in Private Homes, Assisted Living Facilities, and Nursing Homes - G. Kevin Randall; Peter Martin; Maurice MacDonald; Jennifer Margrett; Alex J. Bishop; Leonard W. Poon (Journal of Aging Research)
We investigated the influence of social relations on health outcomes in very late life by examining the support-efficacy convoy model among older adults who resided in three different residential environments (centenarians in private homes, n=126; centenarians in assisted living facilities, n=55 ; centenarians in nursing homes, n=105). For each group, path analytic models were employed to test our hypotheses; analyses controlled for sex, mental status, education, perceived economic sufficiency, and activities of daily living. The hypothesized relationships among the models' variables were unique to each of the three groups; three different models fit the data depending upon residential environment. The direct and indirect effects of social relations assessments were positive for the mental and physical health of very old adults, suggesting that participants welcomed the support. However, residential status moderated the associations between the assessments of social relations, self-efficacy, and both outcomes, physical and mental health.